2012
DOI: 10.3390/ijms131013030
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Phage Display Derived Peptide CaIX-P1 on Human Colorectal Carcinoma Cells Correlates with the Expression of Carbonic Anhydrase IX

Abstract: Phage display represents an attractive screening strategy for the identification of novel, specific binding ligands that could be used for tumor targeting. Recently, a new peptide (CaIX-P1) with affinity for human carbonic anhydrase IX (CAIX) was identified and evaluated. The aim of the present study is to characterize the properties of CaIX-P1 for targeting human colorectal carcinoma and investigate the correlation of peptide binding with the expression of carbonic anhydrase IX. Human colorectal carcinoma HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…So as Figure 2 shows, a much higher uptake of gold was found in HT29 cells treated with GNR/anti-CAIX in contrast with GNR-PEG and medium control, indicating efficient targeting and successful conjugation. Also, hypoxic status did increase intracellular accumulation of GNRs treated with GNR/anti-CAIX at 2 h, which is in agreement with previous studies by showing a positive correlation between CAIX conjugates binding and expression of CAIX in human carcinoma cells [ 29 , 30 ]. Hyperspectral dark field microscopy imaging also confirmed similar findings with the GNR/anti-CAIX group showing strong and specific binding to HT29 cells compared to the control group, while the GNR-PEG group only showing non-specific binding ( Supplementary Figure 3 ).…”
Section: Resultssupporting
confidence: 92%
“…So as Figure 2 shows, a much higher uptake of gold was found in HT29 cells treated with GNR/anti-CAIX in contrast with GNR-PEG and medium control, indicating efficient targeting and successful conjugation. Also, hypoxic status did increase intracellular accumulation of GNRs treated with GNR/anti-CAIX at 2 h, which is in agreement with previous studies by showing a positive correlation between CAIX conjugates binding and expression of CAIX in human carcinoma cells [ 29 , 30 ]. Hyperspectral dark field microscopy imaging also confirmed similar findings with the GNR/anti-CAIX group showing strong and specific binding to HT29 cells compared to the control group, while the GNR-PEG group only showing non-specific binding ( Supplementary Figure 3 ).…”
Section: Resultssupporting
confidence: 92%
“…However, the high level of CA-IX expression in MDA-MB-231 cells under normoxic conditions has been observed in several studies 64 . The density-dependent CA-IX up-regulation has been demonstrated for several cell lines including MDA-MB-231 65 - 67 . Culture conditions with a high cell density might create a pericellular hypoxic environment, leading to the accumulation of HIF-1 and subsequently CA-IX expression.…”
Section: Discussionmentioning
confidence: 96%
“…Culture conditions with a high cell density might create a pericellular hypoxic environment, leading to the accumulation of HIF-1 and subsequently CA-IX expression. It is difficult to control the pericellular microenvironment completely; therefore, the poor reproducibility of CA-IX expression in MDA-MB-231 cells has been demonstrated 65 . VHL binds to HIF-1α hydroxylated by oxygen, leading to the degradation of HIF-1α and the subsequent prevention of CA-IX expression; therefore, under hypoxic conditions, nonhydroxylated HIF-1α is not recognized by the VHL protein, and RCC4-VHL cells should show CA-IX expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Askoxylakis et al [ 179 ] suggested that expression of the CA-IX protein is unstable, and microenvironment-dependent. The scientific literature lacks information about the onset of CA-IX expression in the course of carcinogenesis, the percentage of CA-IX-positive cells, and the amount of protein expressed in tumour tissues at different disease stages.…”
Section: Immunoliposomementioning
confidence: 99%
“…Thus, more research is needed in order to design a proper treatment regime for patients. The first identified peptide ligand for the CA-IX receptor through phage display technology is CaIX-P1 [ 179 , 180 ]. However, to the best of our knowledge, the endogenous ligand of the CA-IX receptor is unknown.…”
Section: Immunoliposomementioning
confidence: 99%